SAT0740-HPR Parity and the risk of developing rheumatoid arthritis: evidence from the malaysian epidemiological investigation of rheumatoid arthritis case-control study. (12th June 2018) - Too, C.L.; Nurul Aain, A.F.; Tan, L.K.; Lau, I.S.; Nor Asiah, M.L.; Salsabil, S.; Heselynn, H.; Nor Shuhaila, S.; Wahinuddin, S.; Gun, S.C.; Eashwary, B.; Mohd Shahrir, M.S.; et al.
Abstract : Background: Recent evidence from epidemiological studies has suggested that reproductive factors may play an important role for rheumatoid arthritis (RA) development. An inverse association was reported in several studies between parity and risk of RA. Objectives: We investigated the association between parity and risk of anti-citrullinated peptide antibody (ACPA)-positive RA and ACPA-negative RA in the Malaysian population. Methods: Data from the Malaysian Epidemiological Investigation of rheumatoid Arthritis (MyEIRA) population-based case control study involving 902 female early RA and 906 age and residential area-matched female controls were analysed. Parity history was assessed through a questionnaire. Parous women were compared with nulliparous women, by calculating odds ratio (OR) with 95% confidence intervals (Cl). Results: Our findings demonstrated that parity was significantly associated with decreased risk of developing RA in the Malaysian population (RA versus controls, 82% vs. 89%, OR 0.58, 95% CI 0.44–0.77, p<0.001). The association between parity and risk of RA was uniformly observed for ACPA-positive RA (OR 0.58, 95% CI 0.43–0.80, p<0.001) and ACPA-negative RA (OR 0.58, 95% CI 0.40–0.84, p<0.01) subsets, respectively. Compared with nulliparous women, the decreased risk was pronounced at the level of three and more live births for both ACPA-positive (OR 0.48, 95% CI 0.34–0.66, p<0.001) and ACPA-negative RA (OR 0.46, 95% CI 0.31–0.68, p<0.001) subsets. Conclusions: Our data demonstrated that parity and level of three and more live births was associated with decreased risk of developing RA in the Malaysian population. The associated decrease risk was observed in both ACPA-positive and ACPA-negative RA subsets. References: [1] Orellano C, Saevardottir S, Klareskog L, Karlson EW, Alfredsson L, Bengtsson C. Parity and the risk of developing rheumatoid arthritis: results from the Swedish Epidemiological Investigation of Rheumatoid Arthritis study. Ann Rheum Dis2014;73:752–755. [2] Ren L, Guo P, Sun Q, Liu H, Chen Y, Huang Y and Cai X. Number of parity and risk of rheumatoid arthritis in women: A dose-response meta-analysis of observational studies. J. Obstet. Gynaecol. Res2017;43(9):1428–1440. Disclosure of Interest: None declared